2014
DOI: 10.3109/1354750x.2014.943291
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of DNA repair genesOGG1, XRCC1, XPDandERCC6in bladder cancer in Belarus

Abstract: Among four DNA repair gene polymorphisms, the OGG1 326 Ser/Cys and XPD 312 Asp/Asn heterozygous genotypes might be recognized as potential genetic markers modifying susceptibility to bladder cancer in Belarus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 61 publications
0
21
0
1
Order By: Relevance
“…Liu et al (20) also revealed that the DNA repair gene ERCC6 rs1917799 polymorphism is associated with gastric cancer risk in the Chinese population. It has also been identified that ERCC6 polymorphisms are associated with susceptibility to oral, lung, bladder and colorectal cancers (21)(22)(23). These findings suggested that ERCC6L may act as an oncogene involved in tumor progression, and may be considered a potential target to aid the efficient diagnosis and development of therapies against breast cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Liu et al (20) also revealed that the DNA repair gene ERCC6 rs1917799 polymorphism is associated with gastric cancer risk in the Chinese population. It has also been identified that ERCC6 polymorphisms are associated with susceptibility to oral, lung, bladder and colorectal cancers (21)(22)(23). These findings suggested that ERCC6L may act as an oncogene involved in tumor progression, and may be considered a potential target to aid the efficient diagnosis and development of therapies against breast cancer.…”
Section: Discussionmentioning
confidence: 96%
“…The rs13181 polymorphism of ERCC2 is a T to G substitution at the 751 locus, which may alter the enzymatic activity of the encoded protein. ERCC2 rs13181 is associated with various cancers, such as gastric cancer, esophageal cancer, non-small cell lung cancer, hepatocellular carcinoma, prostate cancer, skin cancer, and bladder cancer (Yin et al, 2013;Zhu et al, 2013;Li et al, 2014;Ramaniuk et al, 2014;Zhu et al, 2014;Yang et al, 2015;Guo et al, 2015). Previous studies have reported the association between the ERCC2 rs13181 polymorphism and glioma development, but the results are inconclusive (Caggana et al, 2001;Wrensch et al, 2005;Yang et al, 2005;Liu et al, 2009;Luo et al, 2013;Rodriguez-Hernandez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…During the extraction of the data, 4 studies were excluded because of insufficient data (10,11), overlapping data (12) or irrelevance to ERCC6 Met1097Val and Arg1230Pro polymorphisms (13). Ultimately, 5 independent studies, including 4 European studies and 1 Asian study, were selected for the meta-analysis (14)(15)(16)(17)(18). All studies were consistent with HWE.…”
Section: Study Characteristicsmentioning
confidence: 99%